Efeitos imediatos do ortostatismo sobre o tempo e amplitude de reflexão da onda de pulso carotídeo e radial - Magalhães, Pedro (2007)
Background: Decreased arterial distensibility associated with orthostatism is known in humans. However, changing in the pulse pressure amplitude and in the time to reflection are not clearly described in healthier young evaluated during tilt test. We tested the hypotesis that orthostatism could lead to early pulse reflection and increase augmentation index in the carotid and in the radial arteries. Methodology: Were studied 32 healthy young male, aged 18 to 38 (mean 25 ± 5 years old). Subjects with history of cardiovascular desease, orthostatic intolerance or in current vasoactive drug therapy were excluded. Carotid and radial augmentaion index was calculated from pressure waveforms recorded manually using tonometry method in supine and 2 minutes after tilt at 70o . Simultaneously, brachial blood pressure was assessed using oscilometric method, so, the carotid blood pressure was estimated from carotid waveforms. Heart rate was calculated from R-R intervals of the electrocardiogram registrated continuously. Differences between means was tested by pared t test. Pearson coefficient (r) was determined to evaluate correlation. Regression (linear or multiple as necessary), and covariance analysis were performed. To test the influence of other variables on the means, covariance analysis was performed and P ≤ 0,05 level was considered for all significance tests. Results: Carotid augmentation index increased significantly (–35,39 ± 12,24% vs –27,75 ± 14,18%, P = 0,002), so, the radial augmentation index increased (84,65 ± 6,54% vs 88,10 ± 4,92%, P = 0,004). The time to reflection (TR) decreased significantly (234 ± 23 ms vs 188 ± 21 ms P = 0,0001). Negative correlation was observed between delta carotid augmentation index and delta pulse pressure carotid (r2 = 0,142, P = 0,026) Orthostatic changing in the carotid systolic blood pressure was not significant (96,02 ± 8,41 mmHg vs 94,71 ± 11,58 mmHg, P = 0,53). So, the same was observed to the rate of pulse pressure amplification (36,21± 18,42% vs 34,00 ± 25,75%, P = 0,681). Conclusions: Upright position during tilt test decreased the time to the pulse wave reflection and increased the carotid and radial augmentation index. Besides, the carotid systolic blood pressure and the rate of pulse pressure amplification were attenuated. These results suggest the role of carotid wave reflection to participate in the orthostatic tolerance mechanisms and human bipedalism adaptation. This approach could have implication on the understanding cardiovascular aging, hypertension and syncope associated with arterial stffness